The Impact of Shared Telecom Infrastructure on Digital Connectivity and Inclusion - Georges V. Houngbonon; Marc Ivaldi; Emil Palikot; Davide Strusani (International Telecommunications Society (ITS), 2023)
A substantial number of individuals remains unconnected to the Internet despite an increasing emphasis on infrastructure-based competition. This paper investigates the impact of shared telecom infrastructure on digital connectivity and inclusion using a new dataset on mobile tower sharing transactions between 2008 and 2020, i.e., acquisitions of towers by independent companies from mobile network operators to be rented back to all operators. Estimates based on differencein- differences with different timing of treatment suggest that these transactions resulted in a significant drop in the price of mobile connectivity as well as an increase in availability and uptake of mobile Internet, especially by rural households and women. Our findings suggest that increased competition intensity through reduced market concentration appears to be the main driver of these outcomes.
Keywords: L96; L14; O14; 330; Mobile Telecommunications; Vertical Integration; Digital Technology Adoption